A Method Sustaining the Bioelectric, Biophysical, and Bioenergetic Function of Cultured Rabbit Atrial Cells - Kirschner Peretz, Noa; Segal, Sofia; Arbel-Ganon, Limor; Ben Jehuda, Ronen; Shemer, Yuval; Eisen, Binyamin; Davoodi, Moran; Binah, Ofer; Yaniv, Yael (Frontiers in Physiology, 2017)
Culturing atrial cells leads to a loss in their ability to be externally paced at physiological rates and to maintain their shape. We aim to develop a culture method that sustains the shape of atrial cells along with their biophysical and bioenergetic properties in response to physiological pacing. We hypothesize that adding 2,3-Butanedione 2-monoxime (BDM), which inhibits contraction during the culture period, will preserve these biophysical and bioenergetic properties. Rabbit atrial cells were maintained in culture for 24h in a medium enriched with a myofilament contraction inhibitor, BDM. The morphology and volume of the cells, including their ability to contract in response to 1-3 Hz electrical pacing, was maintained at the same level as fresh cells. Importantly, the cells could be successfully infected with a GFP adenovirus. Action potentials, Ca2+ transients, and local Ca2+ spark parameters were similar in the cultured and in fresh cells. Finally, these cultured cells’ flavoprotein autofluorescence was maintained at a constant level in response to electrical pacing, a response similar to that of fresh cells. Thus, eliminating contraction during the culture period preserves the bioelectric, biophysical and bioenergetic properties of rabbit atrial myocytes. This method therefore has the potential to further improve our understanding of energetic and biochemical regulation in the atria.